Early High-Dose Methylprednisolone Therapy Is Associated with Better Outcomes in Children with Acute Necrotizing Encephalopathy - Han-Pi Chang; Shao-Hsuan Hsia; Jainn-Jim Lin; Oi-Wa Chan; Chun-Che Chiu; En-Pei Lee (MDPI AG, 2022)
Background: The neurologic outcomes of acute necrotizing encephalopathy (ANE) are very poor, with a mortality rate of up to 40% and fewer than 10% of patients surviving without neurologic deficits. Steroid and immunoglobulin treatments have been the most commonly used options for ANE, but their therapeutic efficacy is still controversial. Method: We retrospectively reviewed the medical records of 26 children diagnosed with ANE. We also divided these patients into two groups: 21 patients with brainstem involvement and 8 patients without brainstem involvement. Pulse steroid therapy (methylprednisolone at 30 mg/kg/day for 3 days) and intravenous immunoglobulin (2 g/kg for 2-5 days) were administered to treat ANE. Results: The overall mortality rate was 42.3%, and patients who did not survive had significantly higher initial lactate and serum ferritin levels, as well as higher rates of inotropic agent use with brainstem involvement. There were no significant differences in the outcomes of pulse steroid therapy or pulse steroid plus immunoglobulin between survivors and non-survivors. When analyzing the time between symptom onset and usage of pulse steroid therapy, pulse steroid therapy used within 24 h after the onset of ANE resulted in significantly better outcomes (p = 0.039). In patients with brainstem involvement, the outcome was not correlated with pulse steroid therapy, early pulse steroid therapy, or pulse steroid therapy combined with immunoglobulin. All patients without brainstem involvement received "early pulse methylprednisolone" therapy, and 87.5% (7/8) of these patients had a good neurologic outcome. Conclusion: Pulse steroid therapy (methylprednisolone at 30 mg/kg/day for 3 days) administered within 24 h after the onset of ANE may be correlated with a good prognosis. Further studies are needed to establish a consensus guideline for this fulminant disease.